The politics of survival - Abélès, Marc (Public planet books, 2010)
The end of the brilliance that the future will bring -- Globalization and the state : a false debate? -- Virtual Europe, a space of uncertainty -- Understanding the displacement of politics : from convivance to survival -- A necessary detour -- From power to humanity -- The economy of survival -- Toward global politics